Prevalence, Specificity, And Risk Factors Of Red Blood Cell Alloimmunization In Chronic Blood Transfusion Therapy: A Retrospective Cohort Study (The Review of Diabetic Studies, 2025)
This retrospective study investigated the burden and prevention of red blood cell alloimmunization in 120 multi-transfused patients at a Saudi Arabian tertiary care center. The overall alloimmunization rate was 18.3%, with anti-E, anti-K, and anti-C being the most common alloantibodies. Alloimmunization was significantly associated with receiving more than 10 transfusions (p=0.02) and a diagnosis of thalassemia major. The core finding was a pronounced protective effect of extended antigen matching. Patients receiving blood units matched beyond ABO and RhD (including Rh variants and Kell) had a significantly lower alloimmunization rate of 7.1%, compared to 24.6% in the standard matching group (p=0.003). These results highlight the clinical significance of Rh and Kell antigen mismatches and demonstrate that extended antigen matching is an effective strategy to mitigate alloimmunization risk in populations requiring chronic transfusion support. Implementing proactive extended phenotyping is recommended to enhance transfusion safety.